Geometric morphometric analysis reveals sexual dimorphism in the distal femur. (February 2016) - Cavaignac, Etienne; Savall, Frederic; Faruch, Marie; Reina, Nicolas; Chiron, Philippe; Telmon, Norbert
Highlights: Distal femur shape varies based on sex. Three-dimensional analysis of the distal femur can be used to predict sex. Geometric morphometric analysis can predict sex. Abstract: An individual's sex can be determined by the shape of their distal femur. The goal of this study was to show that differences in distal femur shape related to sexual dimorphism could be identified, visualized, and quantified using 3D geometric morphometric analysis. Geometric morphometric analysis was carried out on CT scans of the distal femur of 256 subjects living in the south of France. Ten landmarks were defined on 3D reconstructions of the distal femur. Both traditional metric and geometric morphometric analyses were carried out on these bone reconstructions; these analyses identified trends in bone shape in sex-based subgroups. Sex-related differences in shape were statistically significant. The subject's sex was correctly assigned in 77.3% of cases using geometric morphometric analysis. This study has shown that geometric morphometric analysis of the distal femur is feasible and has revealed sexual dimorphism differences in this bone segment. This reliable, accurate method could be used for virtual autopsy and be used to perform diachronic and interethnic comparisons. Moreover, this study provides updated morphometric data for a modern population in the south of France.